Women-Led Businesses: An Ethnographic Study of Gendered Entrepreneurship in Gilgit-Baltistan, Pakistan. (December 2020) - Dinar, Humera
As a result of the growing global economy and a development model with entrepreneurialism at its heart, women in remote and high-mountain societies in Gilgit-Baltistan, the northernmost part of Pakistan, have begun to venture outside the traditional and gendered economies by embarking on new forms of income-generating activities. This ethnographic study of women entrepreneurs in Gilgit-Baltistan, Pakistan, provides a critical analysis of the promotion of women's entrepreneurship as a key strategy by development organizations to address gender inequities. The ethnographic accounts of women's diverse experiences as entrepreneurs featured in this article demonstrate that the neoliberal development model and the global capitalist market serve as an opportunity for women in these high-mountain communities that allows them to push against socio-cultural pressures. Within these environments, women strive to become economic actors and make space for themselves in conventionally male-dominated economic trades such as business and entrepreneurship. In contrast to the NGOs' narratives that glorify women as entrepreneurs in uncontentious ways, my ethnographic research views women as complex subjectivities whose lived experiences are embedded within socio-economic, religious and political dimensions of notions of legitimacy that dictate women's participation in public spaces. The ethnographic accounts in this article illustrate how women navigate, negotiate, contest and reproduce the patriarchal sovereignties and development regimes.